MOVPE grown self-assembled and self-ordered InSb quantum dots in a GaSb matrix assessed by AFM, CTEM, HRTEM and PL - Mock, P; Booker, G; Mason, N; Nicholas, R; Aphandery, E; Topuria, T; Browning, N (2001)
Self-assembled InSb quantum dots (QDs) were grown by metal-organic vapour phase epitaxy (MOVPE) in a GaSb matrix. Atomic force microscopy (AFM), conventional diffraction contrast transmission electron microscopy (CTEM), high resolution transmission electron microscopy (HRTEM), and photoluminescence (PL) were used for the assessment of the QDs. Reductions in the (III)/v, ratios and growth rates resulted in a change of the morphology of the InSb islands from hillocks without facets, and a low level of order to dumbbell shaped islands with distinct facets and a higher level of order. (C) 2001 Published by Elsevier Science B.V.